2003
DOI: 10.1007/s00114-002-0389-9
|View full text |Cite
|
Sign up to set email alerts
|

Autopoiesis: a review and a reappraisal

Abstract: The aim of the paper is to review critically the notion of autopoiesis as presented by Maturana and Varela. In particular, recognizing that there are difficulties in obtaining a complete and clear picture from the primary literature, an effort is made to present a coherent view-also based on many years of personal contact with Francisco Varela. The paper begins with a few historical notes to highlight the cultural background from which the notion of autopoiesis arose. The basic principles of autopoiesis as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
124
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(133 citation statements)
references
References 34 publications
0
124
0
9
Order By: Relevance
“…The autopoietic theory was also centered on the membrane but focused on self-maintenance rather than on (self-)reproduction. [3,4] However, such a self-maintaining system could also enter a self-reproduction mode, manifested by growth, if homeostatic misbalance leads to excess membrane formation as shown in a thought experiment by Luisi. [3] In this progress report, we review the existing approaches for growth of compartments in the context of bottom-up synthetic biology and protobiology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The autopoietic theory was also centered on the membrane but focused on self-maintenance rather than on (self-)reproduction. [3,4] However, such a self-maintaining system could also enter a self-reproduction mode, manifested by growth, if homeostatic misbalance leads to excess membrane formation as shown in a thought experiment by Luisi. [3] In this progress report, we review the existing approaches for growth of compartments in the context of bottom-up synthetic biology and protobiology.…”
mentioning
confidence: 99%
“…[3,4] However, such a self-maintaining system could also enter a self-reproduction mode, manifested by growth, if homeostatic misbalance leads to excess membrane formation as shown in a thought experiment by Luisi. [3] In this progress report, we review the existing approaches for growth of compartments in the context of bottom-up synthetic biology and protobiology. We consider mainly micrometer-sized compartments due to their characteristic cellular dimensions; this feature also ensures that the area and curvature of the interface or the bounding membrane has less influence on the enclosed solution.…”
mentioning
confidence: 99%
“…[34] The minimal criteria defining autopoiesis should verify whether 1) the system has a semipermeable boundary that is 2) produced within the system and 3) that encompasses reactions that regenerate the components of the system. [35] Minimal autopoietic systems were then chemically designed in micellar and vesicular systems by Luisi et al,w ho described the autocatalysist aking place in the nonreversible formation of some surfactant molecules. [36,37] In our originally discussed case of dynamic surfactants, [33] a biphasic environment was observed at the early stage of the autocatalytic formation of micelles owing to emulsions of the hydrophobic aldehyde, ap henomenont hat could also participate in the complexity of the system.…”
Section: Introductionmentioning
confidence: 94%
“…Many such treatises assume that chiral selection has occurred under abiotic conditions, and preceded (or even served as a prerequisite for) life's origin. Among these are models that involve bifurcation in small molecules [8-10] In parallel, systems were reported that involve polymerization [11,12] as well as interactions within crystals (reviewed in [12]). The basic principles that guide such papers include the notion of statistical fluctuations, namely that in an ensemble of asymmetric molecules of a given type, there will always be an excess of one enantiomer, particularly apparent in small ensembles, and that such fortuitous excess may be greatly amplified by catalytic or replicative reactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Life is believed to have emerged by self organization processes occurring within a random and highly heterogeneous chemical environment [10,13]. One of the hallmarks of some other prebiotic evolution studies is the assumption that homochirality (the prevalence of only one of the two chiral isomers), widespread in present-day life, has emerged as part of the processes that led to cellular life [14-19].…”
Section: Introductionmentioning
confidence: 99%